Intraindividual Neurofilament Dynamics in Serum Mark the Conversion to Sporadic Parkinson's Disease - Wilke, Carlo; Santos, Marcia Cristina Teixeira; Schulte, Claudia; Deuschle, Christian; Scheller, Dieter; Verbelen, Moira; Brockmann, Kathrin; Thaler, Anna‐Katharina; Sünkel, Ulrike; Roeben, Benjamin; Bujac, Sarah; Metzger, Florian G.; et al. (Movement disorders, 2020)
Background and Objectives With disease‐modifying treatment strategies on the horizon, stratification of individual patients at the earliest stages of Parkinson's disease (PD) is key—ideally already at clinical disease onset. Blood levels of neurofilament light chain (NfL) provide an easily accessible fluid biomarker that might allow capturing the conversion from prodromal to manifest PD. Methods We assessed longitudinal serum NfL levels in subjects converting from prodromal to manifest sporadic PD (converters), at‐risk subjects, and matched controls (72 participants with ≈4 visits), using single‐molecule array (Simoa) technique. Results While NfL levels were not increased at the prodromal stage, subjects converting to the manifest motor stage showed a significant intraindividual acceleration of the age‐dependent increase of NfL levels. Conclusions The temporal dynamics of intraindividual NfL blood levels might mark the conversion to clinically manifest PD, providing a potential stratification biomarker for individual disease onset in the advent of precision medicine for PD. © 2020 The Authors. Movement Disorders published by Wiley Periodicals, Inc. on behalf of International Parkinson and Movement Disorder Society.